(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
The article analyses Levinas’s notion of subjectivity and examines its possible links with the notion developed by Kant, understood the latter as an exemplary vision of the modern explanation of subjectivity. Hofmeyr’s position is discussed, who argues that there was a paradigmatic shift between an "early Levinas" centred on a freedom of Kantian type, and a "later Levinas" focused on passivity and that transcends Kant. The article shows that subjectivity in Levinas can never be understood as an activity in the Kantian sense.